IDENTIFIKASI INDIKATOR KINERJA UNTUK MENGUKUR KEBERHASILAN PADA PROYEK KONSTRUKSI JALAN BETON BERDASARKAN PERSPEKTIF PENYEDIA JASA KONSTRUKSI - Safari, Athiah; Solikin, Mochamad; Sunarjono, Sri; Handayani, Fajar Sri; Harnaeni, Senja Rum (Politeknik Negeri Semarang, 2024)
One of the infrastructures that society absolutely needs is roads. With the existence of roads, land transportation activities are carried out so that economic and social mobility runs normally. Concrete is one of the materials commonly used for road pavements, where this material technology has many advantages such as being able to withstand heavy vehicle loads and lower maintenance costs. To produce quality concrete roads, the role of the manager who leads the concrete road construction project is very decisive. To produce a quality concrete road, a manager must be able to determine indicators that influence its success, so that construction activities run effectively and efficiently. This study aims to identify Key Performance Indicators (KPIs) that can be used as a measure of success in concrete road construction projects based on the perspective of construction service providers. The analytical method used in this study is the Relative Importance Index to determine performance indicators that can be used as KPIs based on their relationship to success in concrete road construction projects. The results of the analysis show that the performance indicators that can affect the success of a concrete road construction project based on the perspective of a construction service provider are cost, quality, time, productivity, and environment, each of which has a weight of 21.41%, 19.44%, 19.05%, 15.65%, 12, 86% and 11.59%.